Glaciers - Newell, Nora (My University, 1893)
Introduction: Although not every one can observe the actions of glaciers in his immediate locality, for they exist only in elevated latitudes and on mountain sides, yet the subject is fascinating and our mountain travel is much more interesting and instructive if we possess some knowledge concerning them.
Citation: Newell, Nora. Glaciers. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Glaciers; Mountains; Knowledge; Theses; Manuscripts (documents)